Social work education : voices from the Asia Pacific - Noble, Carolyn; Henrickson, Mark; Han, In Young (Sydney University Press, 2013)
In this second edition we hear four new voices, from Cambodia, Fiji, Japan and Vietnam, together with revised and updated chapters from social work educators in Australia, China, Hong Kong, India, Korea, Nepal, and New Zealand.